Pendekatan Korelasi Kandungan Fraksi Halus dalam Menentukan Potensi Plastisitas pada Lempung Berplastisitas Rendah - Saputra, Hendra (Jurnal Teknik Sipil, 2025)
This research proposes an alternative model for predicting the plasticity potential of clay soils, updating the previous model developed by Firincioglu and H. Bilsel. The alternative lies in the use of the fine fraction content (FC) as the predictive variable, replacing the percentage of sand fraction content (SC) previously suggested. The analysis was conducted on 61 low-plasticity clay (CL) soil samples, classified using the Casagrande and Moreno-Maroto systems, by examining the relationship between consistency limits (LL, PI), grain fractions (sand, silt, clay), and related parameters (FC, sand-silt-clay spectrum, and sand fraction ratio). The correlation analysis results show significant findings, including a strong positive correlation between sand content and the sand ratio (SR), as well as a negative correlation between sand content and FC, and between FC and SR. The performance of the substitute Casagrande quadratic model [2] reveals the best predictive accuracy among the proposed models ( [1], R² =0.90; [3], R²  0.89; [4], R² =0.43; [5], R² =0.93; [6], R² =0.93; [7], R² =0.89; [8], R² =0.89), with the highest R2 value of 0.93, MSE of ≈4.01, and MAE of ≈1.44–1.47. The equation is .